Menguraikan Solusi Dalam Masalah Peningkatan Sharia Compliance - Wendah Asyani; Fathurrahman Djamil; Aries Safari (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2019)
The meaning of sharia compliance in sharia banks in concept is actually the application of the principles of Islam, sharia, and tradition in financial and banking transactions and other related businesses consistently, and making sharia as a framework for the system and finance of sharia banks in the allocation of resources, management, production, capital market activities, and wealth distribution. However, until now, there are various problems in assessing the implementation of sharia compliance. Judging from the overlapping Sharia Supervisory Board while on the other hand, the capacity of external sharia auditors lacks sufficient competence because it refers to conventional audit procedures. The purpose of this study is to determine priority problems and appropriate solutions to improve the implementation of sharia compliance. This study uses the ANP analysis method that outlines the problems faced in the implementation of sharia compliance and appropriate solutions to overcome these problems. The results show that knowledge and guidelines are the main problems being faced by various parties where alternative solutions are creating new sharia product innovations, the aim is to force various parties both internally and externally to understand sharia concepts in line with economic concepts. The second solution is to hold a training program related to the problem at hand, with the training expected to be able to reach an agreement to form a guideline.